A rethink of the incentives programme in the conservation of South Korea's historic villages. Issue 2 (17th August 2015) - Mat Radzuan, Indera Syahrul; Inho, Song; Ahmad, Yahaya
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to address the overarching question, which was whether the incentives programmes formulated for the community have been found to be suitable to the aspirations and needs of the local residents. Design/methodology/approach – This study has resulted from the authors' experience through conducting a survey with the local residents in three locations, namely the Bukchon Hanok Village located at Seoul metropolitan city; the Hahoe Village, Angdong and the Yangdong Village, Gyeongju; both the latter are located towards the west of the Korean peninsula in the Gyeongbuk-do Province. This study has hopefully tried to analyse the residents' perception of the effectiveness of the current incentives policy by using the Bennett's programme evaluation method. Findings – Results show that there was a divergent direction between the current incentives policy and the local aspirations between sites. In most cases, the cultural heritage conservation has been found to be a catalyst to fulfil a heritage tourism advantage rather than to cater to the local community needs. Originality/value – The paper is the first insightful study of the historic villages which attempts to draw out the importance of the effectiveness of the incentives programme in guiding the conservation efforts for the local economic development.